The impact of Claudio Gutiérrez on my academic formation - Coronado Céspedes, Guillermo (2024)
This contribution is a letter from a student to his professor, an affective transcription of gratitude. Don Claudio Gutiérrez Carranza is presented, through memories, as more than a lecturer. The author walks through texts, philosophical currents, geographical locations and anecdotes to give an account of his relationship with one of the most important thinkers of Costa-Rican philosophical thought.